(untitled) (Sociologisk Forskning, 2017)
Stigmatization and racism in the Swedish migration talk and the diasporic resistance This article argues that the objectifying and stigmatizing characteristics ascribed to the refugee and immigrant populations in the current Swedish refugee debate and the existing discriminatory and racializing practices in Sweden should be analyzed far beyond the recent refugee problematic and the global terrorism related to the political Islam. This study upholds in that way that the practices of objectification, stigmatization, racialization and exclusion get strength from a broader and deeper political context. In this context, the existence of a race biological institute, the project of the Swedish folkhem and its cultural boundaries, the emergence of a systematic discrimination against refugees and immigrants since the mid-1980s and related acts of violence depict the outlines of a white and (mono)cultural Swedish ”imagined community” which disregards the power, dynamism and subjectivity of immigrant and refugee groups. In this respect, the notion of diaspora, which will be illustrated by the Kurdish diaspora in Sweden, constitutes an important platform of resistance as it claims the political recognition for other ethnicities than the native Swede.